Finding the Right Balance between Generalization and Specialization in Software Design - Ritu Godbole (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article explores the critical challenge of balancing generalization and specialization in modern software architecture design. It comprehensively analyzes various research studies and examines how organizations navigate this architectural decision-making process. The article investigates the impact of balanced architectural approaches on system quality, maintainability, and performance. Key findings demonstrate that generalized designs offer flexibility and reusability while specialized implementations provide optimized performance and context-specific solutions. The article presents evidence-based strategies for achieving an optimal balance through modular architecture, pattern integration, and systematic testing approaches. It also explores best practices for implementation, including the evolution from generic to specialized designs and the importance of comprehensive documentation and testing strategies.